2006
DOI: 10.2478/s11532-006-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of ammonia. N2H4-an intermediate reaction product

Abstract: The paper reports the thermal decomposition of ammonia under dynamic conditions at 800• C in a quartz reactor. Its purpose is to confirm the homogeneous-heterogeneous degenerated branched chain mechanism established in previous studies, which assume the formation of N 2 H 4 as a molecular intermediate; this paper identifies hydrazine as a product of thermal decomposition using FT-IR and UV-VIS spectroscopies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 11 publications
2
32
0
1
Order By: Relevance
“…As compared with the relatively low SI‐DRIFTS spectrum of S‐Pt‐C 3 N 4 under dark conditions, the characteristic peaks were significantly enhanced under light irradiation (Figure C). More specifically, the peak at 821 cm −1 is attributed to the breathing vibration of heptazine rings, and the peak at 1006 cm −1 is indexed to the N−H bending vibration . The broad band at 1200–1700 cm −1 corresponds to the stretching vibration mode of CN heterocycles with peaks positioned at 1697, 1493, and 1341 cm −1 .…”
Section: Figurementioning
confidence: 99%
“…As compared with the relatively low SI‐DRIFTS spectrum of S‐Pt‐C 3 N 4 under dark conditions, the characteristic peaks were significantly enhanced under light irradiation (Figure C). More specifically, the peak at 821 cm −1 is attributed to the breathing vibration of heptazine rings, and the peak at 1006 cm −1 is indexed to the N−H bending vibration . The broad band at 1200–1700 cm −1 corresponds to the stretching vibration mode of CN heterocycles with peaks positioned at 1697, 1493, and 1341 cm −1 .…”
Section: Figurementioning
confidence: 99%
“…Experimental data from [11] performed at 1073 K, 1 atm and in a quartz reactor, showed that after 60 s, 40% of NH 3 is decomposed. However, under the same condition, current simulations predict only a 5% decomposition of NH 3 .…”
Section: Surface Reactionsmentioning
confidence: 99%
“…Ge 3 N 4 nanowires were growing on the surface of Ge source, while InP NWs were formed on the Si substrate, located at 2 cm above the source. At elevated temperatures the Ge and InP surfaces served as catalysts and N 2 H 4 was decomposed through the fast chain reactions, forming active transient nitrogen precursors (NH 2 , NH, N) until finally the stabile N 2 , NH 3 and H 2 molecules were formed [13][14][15] . The Mc Bain quartz spiral microbalance was used for the analysis of the interaction of Ge source with hydrazine that was containing different amount of water.…”
Section: Methodsmentioning
confidence: 99%